Improvement of Static Voltage Stability of 16-Bus Bali System by Optimal Placement of SVC - Ni Putu Agustini; I Made Wartana; Abraham Lomi (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2021)
In a power system, the reactive power imbalance is related to the stability of the static voltage because the injection of reactive power that the bus receives from the system determines the bus's capability in the system. Rapid increases in real and reactive power losses occur as the system approaches the voltage drop point or the maximum load point. It is necessary to support local and adequate reactive power to avoid system leading to be voltage collapse. This study analyzes the improvement of the margin of static voltage stability using one type of modern control equipment of shunt flexible AC transmission system (FACTS), namely the static var compensator (SVC). The controller's representations are used in the continuation power flow (CPF) process to study static voltage stability. The proposed method's effectiveness has been investigated using a practical test system, namely the Bali 16-bus system, to increase the system loading capacity. The simulation was carried out by installing a modern controller in the best location, namely on bus 07 ASARI; an increase in system margin loading closed to 2% compared to the base case condition, namely λmax = 1,879 p.u with the voltage profile not changing significantly.